Headache in healthcare workers related to personal protective equipment use in COVID-19 referral hospital - Ida Ayu Sri Wijayanti; Ni Putu Ayu Putri Mahadewi; Putu Gede Sudira; Kumara Tini; Ni Made Susilawathi; I Made Oka Adnyana (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundStudies show that wearing personal protective equipment (PPE) for long periods of time can lead to discomfort such as headaches, which could affect the performance of healthcare workers. The aim of this study was to determine the prevalence and risk factors of headaches related to PPE in healthcare workers at a COVID-19 referral hospital. MethodsA cross-sectional study was conducted involving 174 healthcare workers in a COVID-19 referral hospital in Bali. We conducted interviews using a questionnaire that consisted of three main parts: characteristics of the subjects, PPE usage, and PPE-associated headaches. A multiple logistic regression was used to analyze the data. ResultsThe analysis results showed that the PPE-associated headaches had a prevalence of 63.8% and were gradual in onset, pressure-like in quality (46%), and mild in intensity (80.1%). PPE level III-associated headache was the most common type. The majority of the participants had headaches up to 6 hours after using the protective gear, but improving within 15-30 minutes of removal and/or after pharmacotherapy. A Chi-squared analysis showed a statistically significant association between duration of PPE use, working units, and PPE levels (p<0.05). A logistic regression analysis found a significant relationship between PPE level and headache occurrence (OR=4.826;95%CI: 2.433-9.572; p<0.001). ConclusionThe frequency of PPE-associated headache was high and the PPE level was a risk factor of headache among healthcare workers. Better strategies are needed to reduce the duration of PPE exposure so that the work performance and quality of life of healthcare workers are not significantly affected.